The Evolution of Endophagy in Herbivorous Insects - Tooker, John F.; Giron, David (Frontiers in Plant Science, 2020)
Herbivorous feeding inside plant tissues, or endophagy, is a common lifestyle across Insecta, and occurs in insect taxa that bore, roll, tie, mine, gall, or otherwise modify plant tissues so that the tissues surround the insects while they are feeding. Some researchers have developed hypotheses to explain the adaptive significance of certain endophytic lifestyles (e.g., miners or gallers), but we are unaware of previous efforts to broadly characterize the adaptive significance of endophagy more generally. To fill this knowledge gap, we characterized the limited set of evolutionary selection pressures that could have encouraged phytophagous insects to feed inside plants, and then consider how these factors align with evidence for endophagy in the evolutionary history of orders of herbivorous insects. Reviewing the occurrence of endophytic taxa of various feeding guilds reveals that the pattern of evolution of endophagy varies strongly among insect orders, in some cases being an ancestral trait (e.g., Coleoptera and Lepidoptera) while being more derived in others (e.g., Diptera). Despite the large diversity of endophagous lifestyles and evolutionary trajectories that have led to endophagy in insects, our consideration of selection pressures leads us to hypothesize that nutritionally based factors may have had a stronger influence on evolution of endophagy than other factors, but that competition, water conservation, and natural enemies may have played significant roles in the development of endophagy.